دور العوامل المؤثرة في سلوك المستهلك في مجال اتخاذ القرار الشرائي - ناصر محمد; ماخوس ديمه (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يتمحور هذا البحث حول دراسة العوامل التي تؤثر في سلوك الأفراد و‘تشِّكل أنماطهم الشرائية، وهذا ما يعطيه أهمية خاصة وضرورة مُلحَّة لكل من المنتجين والمسوقين، نظراً لما لهذه العوامل من دور كبير في تحليل العملية الشرائية التي يقوم بها المستهلك، ومن خلال ذلك يكون الهدف منه هو إيجاد تفسيرات للسلوك الذي يتبعه المستهلك في عملية الشراء بناءً على جملة العوامل المؤثرة في اتخاذه القرار الشرائي، لأن ذلك سيساعدهم في تصريف سلعهم بصورة مناسبة ومرضية للمستهلك، وإسقاط ذلك في إطار الدراسة الميدانية لمعرفة أهم العوامل التسويقية والفردية والبيئية لمستهلك سلع الصناعات الكيميائية، وقد انتهى البحث إلى عدد من النتائج والتي على أساسها تم وضع المقترحات التي يراها الباحث مناسبة لتحقيق الهدف المنشود من البحث وأهمها ضرورة تركيز الشركات المصنعة للسلع الكيميائية على الإعلان بوصفه عنصراً هاماً في المزيج التسويقي، فضلاً عن التركيز على العوامل الجغرافية والسكانية والطبقات الاجتماعية لما لها في تأثير في الأنماط الشرائية للأفراد وبالتالي على سلوكهم الشرائي. This research is focusing on the study of the factors that have influence on the individuals’ behavior and form their purchasing manners, that gives it special importance and urgent need for both producers and marketers because these factors have an important role in analyzing the purchasing process of the consumer, so the aim of it is to find an explanation for the consumer’s behaviour in the purchasing process based on the combination of the factors active while he is making his purchase decision, because this will help them in selling their products in a suitable and satisfying way for the consumer. Further, the research aims to apply that, in the frame of the practical study to know the most important marketing, individual and environmental factors of the chemical industrial products’ consumer This research has reached many results and recommendations based on which the recommendations considers suitable to achieve the required results of the study, the most important of which is that companies of chemical industries must give more importance to advertising as an important element in the marketing mix, in addition to concentrating on the geographic, demographic and social classes for their influence on the purchasing manners of individuals and consequently on their purchasing conduct.